2014
DOI: 10.3109/09553002.2014.938278
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced cognitive impairment and altered diffusion tensor imaging in a juvenile rat model of cranial radiotherapy

Abstract: Purpose Assess the long term effects of fractionated whole brain irradiation (fWBI) using diffusion tensor imaging (DTI) and behavior in a pediatric rodent model for the clinical presentation of adult pediatric cancer survivors. Materials and Methods Five week old, male F344xBN rats were randomized to receive 0, 5, or 6.5 Gy fractions biweekly for 3 weeks, resulting in Sham, Irradiated-30 (IR-30) and IR-39 Gy total dose groups. Magnetic Resonance Imaging occurred at 1, 3, 6 and 9 months with behavioral asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In children and adults who survive radiation therapy for brain cancer, decreases in FA in white matter have been reported ( 30 , 31 ). In rats, other authors have variably shown a decrease in FA in the corpus callosum 1 year after large single WBI doses ( 32 ) or no change after fractionated irradiation with larger bioequivalent doses than we used ( 33 , 34 ). Further work is needed using clinically relevant doses at later time points and including other diffusion tensor imaging parameters, such as mean diffusivity, and areas other than the corpus callosum, such as the fimbria, that have been implicated in hippocampal impairment ( 35 ) before the value of MRI in imaging white matter changes can be fully evaluated.…”
Section: Discussionmentioning
confidence: 49%
“…In children and adults who survive radiation therapy for brain cancer, decreases in FA in white matter have been reported ( 30 , 31 ). In rats, other authors have variably shown a decrease in FA in the corpus callosum 1 year after large single WBI doses ( 32 ) or no change after fractionated irradiation with larger bioequivalent doses than we used ( 33 , 34 ). Further work is needed using clinically relevant doses at later time points and including other diffusion tensor imaging parameters, such as mean diffusivity, and areas other than the corpus callosum, such as the fimbria, that have been implicated in hippocampal impairment ( 35 ) before the value of MRI in imaging white matter changes can be fully evaluated.…”
Section: Discussionmentioning
confidence: 49%
“…Gy is enough to cause cognitive dysfunction [4]. There is no doubt that radiation damage caused by high doses of radiation, but accumulating evidence suggests that various degrees of cognitive deficit can develop after much lower doses of ionizing radiation, as well [21]. A recent study showed that the longer the exposure, the greater the degree of brain damage [33].…”
Section: Factors Influencing Radiation-related Cognitive Impairmentmentioning
confidence: 99%
“…Although hippocampal injury is considered as one of the important causes of cognitive dysfunction caused by RT, some studies have found that non-hippocampal injury also can cause cognitive dysfunction, which may be related to acute and chronic vascular changes [20]. Recently results suggest that the brain white matter damage may not be a direct result of radiation but the more complicated interaction between fractionation, dose per fraction and ability of the tissue type to repair based on blood vessel density [21]. Accumulating evidence suggests that the capillary density will also be sparse when the dose of ionizing radiation is enough, and this may result in different degrees of cognitive impairment [22].…”
mentioning
confidence: 99%
“…Irradiation of 10 Gy/1 f on C57BL/6J mice did not change the time spent on familiar objects and novel objects 10 to 11 weeks [42] post-irradiation, while it decreased the time spent on novel objects 12 weeks post-irradiation. Acharya implemented a series of studies evaluating the effects of neural stem cells transplantation on brain injury with the use of novel location recognition test [64][65][66][67][68]. After receiving irradiation of 10 Gy/1 f, twomonth-old athymic nude rats demonstrated a decrease of exploration ratio 1 to 4 months post-irradiation and no significant change of exploration ratio 8 months post-irradiation [47][48][49].…”
Section: Morris Water Mazementioning
confidence: 99%